2004
DOI: 10.1177/172460080401900212
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association of Cyp1B1*3 Polymorphism and Ovarian Cancer in a Caucasian Population

Abstract: CYP1B1 is the enzyme with the highest efficiency of conversion of estradiol to 4-hydroxyestradiol in humans. This metabolite has a well-known carcinogenic effect interacting with genomic DNA and has been hypothesized to be partly responsible for the role played by estrogens in ovarian cancer development. A polymorphism has been described for this enzyme causing a Leu to Val substitution in position 432 (CYP1B1*3). The Val432 allele has a higher efficiency of conversion of estradiol to 4-hydroxyestradiol and ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 2 publications
0
11
0
Order By: Relevance
“…Risks were increased for both Asian and Caucasian subjects and were higher among smokers, nulliparous women, and never users of oral contraceptives. In contrast, Cecchin et al (41) found no association of the CYP1B1 L432V allele with ovarian cancer risk in a study of 223 Caucasian cases and 280 controls. The present study, which is larger than either of these reports, found no association with ovarian cancer risk for the L432V, R48G, or A199S polymorphisms.…”
Section: Discussionmentioning
confidence: 94%
“…Risks were increased for both Asian and Caucasian subjects and were higher among smokers, nulliparous women, and never users of oral contraceptives. In contrast, Cecchin et al (41) found no association of the CYP1B1 L432V allele with ovarian cancer risk in a study of 223 Caucasian cases and 280 controls. The present study, which is larger than either of these reports, found no association with ovarian cancer risk for the L432V, R48G, or A199S polymorphisms.…”
Section: Discussionmentioning
confidence: 94%
“…In a larger population-based study (503 cases and 609 controls) with a more comparable population (92% Caucasian and 8% African-American) done by Sellers et al (9), no association with the CYP1B1 Arg 48 Gly, Ala 119 Ser or Leu 432 Val polymorphisms and ovarian cancer risk was seen in single polymorphism models for either racial group. Another population-based study of 223 cases and 280 controls done in Italy also found no association between the CYP1B1 Val 432 Leu polymorphism and epithelial ovarian cancer (12).…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is the first study that has examined the association between ovarian cancer and the CYP1A1 m3 polymorphism, which is found only in individuals of African descent. Although we were underpowered to make precise risk estimates, we did observe ''0000''/''0000'' 40 (14) 91 (20) 38 (14) 64 (14) 1.5 (0.8-2.7) 2 (6) 4 (3) 40 (13) 68 (12) 1.6 (0.9-2.7) ''0000''/''1100'' 1 (<1) 0 (0) 10 (30) 28 ( (4) 29 (9) 40 (7) 2.1 (1.1-3.9) ''1110''/''0011'' 32 (12) 51 (11) 1.5 (0.8-2.9) 1 (3) 1 (1) 33 (11) 52 (9) 1.6 (0.9-3.0) ''1110''/''1100'' 1 (<1) 4 (<1) 4 (12) 11 (9) 1.9 (0. (11) 33 (7) 5 (15) 27 (21) 35 (11) 60 (10) *Wild-type genotype = 0.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…148). However, a recent negative study found no difference between 432V/V cases and controls in Caucasians (149). In the first (positive) study, a significant increase in risk was seen in smokers who carried at least one CYP1B1 432V allele, CYP1A1 (MspI) m2 allele, one COMT Met allele, or two CYP1A2 A alleles compared with never-smokers who carry CYP1A1 (MspI) m1/m1, CYP1B1 L/L, COMT V/V, or CYP1A2 A/A alleles (148).…”
Section: Mol Cancer Res 2006;4(3) March 2006mentioning
confidence: 99%